Process chain of a twin-roll cast aluminium-copper-lithium alloy - Mallow, Sina; Broer, Jette; Milkereit, Benjamin; Grydin, Olexandr; Hoyer, Kay-Peter; Garthe, Kai-Uwe; Milaege, Dennis; Boyko, Viktoriya; Schaper, Mirko; Kessler, Olaf (Production Engineering)
Abstract Rolling processes of conventional cast Al-Li alloys quickly reach their limits due to relatively poor material formability. This can be overcome by using twin-roll casting to produce thin sheets. Further thermomechanical treatment, including hot or cold rolling, and heat treatment can adjust the mechanical properties of twin-roll cast Al-Li sheets. The whole manufacturing chain requires detailed knowledge of the precipitation and dissolution behavior during heating, soaking and cooling, to purposefully select any process parameters. This study shows the process chain of a twin-roll cast Al–Cu–Li alloy achieving a hardness of around 180 HV1 by adapting the heat treatment parameters for homogenisation, hot rolling and age hardening. Both hardness and microstructure evolution are visualised along the process chain.

Numerical and Experimental Investigation of Twin-Roll Casting of Aluminum–Lithium Strips - Grydin, Olexandr; Garthe, Kai-Uwe; Yuan, Xueyang; Broer, Jette; Keßler, Olaf; Králík, Rostislav; Cieslar, Miroslav; Schaper, Mirko (Light Metals 2023)

3D-structure of intermetallic interface layer in Al–steel clad material - Šlapáková, Michaela; Kihoulou, Barbora; Veselý, Jozef; Minárik, Peter; Fekete, Klaudia; Knapek, Michal; Králík, Rostislav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Vacuum)
This paper reveals the 3D character of the intermetallic layer at the aluminum–steel interface which pops up above the original sample surface during annealing. Popping out of the intermetallics was proven using atomic force microscopy. The phase expands out of the plane due to the exothermic formation of the Al5Fe2 phase and the feasibility of surface diffusion. Milling by a focused ion beam enabled the comparison of the chemical composition of the surface layer with the bulk interface, showing no difference. The growth direction is both towards aluminum and steel — the main diffusion flux is from aluminum towards steel, and the new intermetallic phase emerges at the steel side. The shortage of Al atoms causes a shift of the intermetallic as a whole towards aluminum.
Keywords: Al-steel clad; twin-roll casting; 3D characterization; atomic force microscopy; diffusion direction; surface growth

Influence of thermo-mechanical joining process on the microstructure of a hypoeutectic aluminium cast alloy - Borgert, Thomas; Neuser, Moritz; Wiens, Eugen; Grydin, Olexandr; Homberg, Werner; Schaper, Mirko (Materials Research Proceedings)
Requirements of multi-material construction involve adjustments to standard joining techniques. Especially the growing importance of integral cast components poses additional engineering challenges for the industry. One approach to achieve these goals are adaptable joining elements formed by friction spinning. This approach uses friction-induced heat to form customisable joining elements to join sheets for different boundary conditions, even for brittle cast materials. It is possible to react immediately to adapt to the joining process inline and reduce the amount of different joining elements. As the joining partner serve casting plates of the aluminium casting alloy EN AC–AlSi9, which is processed in the sand casting. Joining hypoeutectic AlSi alloys constitutes a challenge because the brittle character of these cause cracks in the joint during conventional mechanical joining. Furthermore, the friction-induced heat of the novel joining process causes a finer microstructure in the hypoeutectic AlSi9 casting alloy. In particular, the eutectic Si is more fine-grained, resulting in higher joint ductility. This study indicates the joining suitability of a hypoeutectic aluminium casting alloy in combination with adaptive manufactured additional joining elements. Here, various mechanical and microstructural investigations validate the influence of the thermomechanical joining technique. In conclusion, the potential of this joining process is presented regarding the joinability of cast aluminium components.

Mechanical and Microstructure Characterisation of the Hypoeutectic Cast Aluminium Alloy AlSi10Mg Manufactured by the Twin-Roll Casting Process - Neuser, Moritz; Schaper, Mirko; Grydin, Olexandr (Journal of Manufacturing and Materials Processing)
Multi-material designs (MMD) are more frequently used in the automotive industry. Hereby, the combination of different materials, metal sheets, or cast components, is mechanically joined, often by forming joining processes. The cast components mostly used are high-strength, age-hardenable aluminium alloys of the Al–Si system. Here, the low ductility of the AlSi alloys constitutes a challenge because their brittle nature causes cracks during the joining process. However, by using suitable solidification conditions, it is possible to achieve a microstructure with improved mechanical and joining properties. For this study, we used the twin-roll casting process (TRC) with water-cooled rollers to manufacture the hypoeutectic AlSi10Mg for the first time. Hereby, high solidification rates are realisable, which introduces a microstructure that is about four times finer than in the sand casting process. In particular, it is shown that a fine microstructure close to the modification with Na or Sr is achieved by the high solidification rate in the TRC process without using these elements. Based on this, the mechanical properties increase, and especially the ductility is enhanced. Subsequent joining investigations validate the positive influence of a high solidification rate since cracks in joints can be avoided. Finally, a microstructure-property-joint suitability correlation is presented.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Influence of Shell Material on the Microstructure and Mechanical Properties of Twin-Roll Cast Al-Si-Mg Alloy - Grydin, Olexandr; Neuser, Moritz; Schaper, Mirko (Conference: ICTP 2023: Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of PlasticityAt: Cannes (France))

HOMOGENIZATION OF TWIN-ROLL CAST Al-Li-BASED ALLOY STUDIED BY IN-SITU ELECTRON MICROSCOPY - CIESLAR, Miroslav; KŘIVSKÁ, Barbora; KRÁLÍK, Rostislav; BAJTOŠOVÁ, Lucia; Grydin, Olexandr; STOLBCHENKO, Mykhailo; Schaper, Mirko (METAL 2022 Conference Proeedings)
Transformation of Fe- and Cu-rich primary phase particles was studied in an Al-Li-based alloy prepared by twin-roll casting. Thin foils for combined STEM and SEM experiments were prepared by electrolytic twin-jet polishing. They were in-situ heated in a TEM heating stage and observed at 200 kV in the JEOL JEM 2200FS electron microscope equipped with STEM HAADF and BF detectors and SEM BSE and SE detectors working both in composition and topographic modes. The resulting structures were combined with EDS mapping performed directly in the heating holder. Dissolution and transformation of Cu- and Fe-rich particles occur above 500 °C. EDS maps acquired on the foil cooled down to room temperature show that Cu and Fe are both still present in newly formed particles, most likely indicating the presence of the Al7Cu2Fe phase.
Keywords: Al-Li-based alloy; in-situ TEM; homogenization; phase transformation

Influence of heat treatment on the suitability for clinching of the aluminium casting alloy AlSi9 - Neuser, Moritz; Böhnke, Max; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In many manufacturing areas, multi-material designs are implemented in which individual components are joined together to form complex structures with numerous joints. For example, in the automotive sector, cast components are used at the junctions of the body and joined with different types of sheet metal and extruded profiles. To be able to join structures consisting of different materials, alternative joining technologies have emerged in recent years. This includes clinching, which allows assembling of two or more thin sheet metal and casting parts by solely cold forming the material. Clinching the brittle and usually less ductile cast aluminium alloys remains a challenge because the brittle character of the cast aluminium alloys can cause cracks during the forming of the clinched joint. In this study, the influence of the heat treatment time of an aluminium casting alloy AlSi9 on the joinability in the clinching process is investigated. Specific heat treatment of the naturally hard AlSi9 leads to a modification of the eutectic microstructure, which can increase ductility. Based on this, it will be examined if specific clinching die geometries can be used, which achieve an optimized geometrical formation of the clinched joint. The load-bearing capacities of the clinched joints are determined and compared by shear tensile and head tensile tests. Furthermore, the joints are examined microscopically to investigate the influence of the heat treatment on the failure behaviour during the load-bearing tests as well as crack initiation within the joining process.
Keywords: Mechanical Engineering; General Materials Science

Influence of solidification rates and heat treatment on the mechanical performance and joinability of the cast aluminium alloy AlSi10Mg - Neuser, Moritz; Grydin, Olexandr; Frolov, Y.; Schaper, Mirko (Production Engineering)
In modern vehicle chassis, multi-material design is implemented to apply the appropriate material for each functionality. In spaceframe technology, both sheet metal and continuous cast are joined to castings at the nodal points of the chassis. Since resistance spot welding is not an option when different materials are joined, research is focusing on mechanical joining methods for multi-material designs. To reduce weight and achieve the required strength, hardenable cast aluminium alloys of the AlSi-system are widely used. Thus, 85–90% of aluminium castings in the automotive industry are comprised of the AlSi-system. Due to the limited weldability, mechanical joining is a suitable process. For this application, various optimisation strategies are required to produce a crack-free joint, as the brittle character of the AlSi alloy poses a challenge. Thus, adapted castings with appropriate ductility are needed. Hence, in this study, the age-hardenable cast aluminium alloy AlSi10Mg is investigated regarding the correlation of the different thicknesses, the microstructural characteristics as well as the resulting mechanical properties. A variation of the thicknesses leads to different solidification rates, which in turn affect the microstructure formation and are decisive for the mechanical properties of the casting as well as the joinability. For the investigation, plates with thicknesses from 2.0 to 4.0 mm, each differing by 0.5 mm, are produced via sand casting. Hence, the overall aim is to evaluate the joinability of AlSi10Mg and derive conclusions concerning the microstructure and mechanical properties.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Clinching as a mechanical joining technique allows a fast and reliable joining of metal sheets in large-scale production. An efficient design and dimensioning of clinched joints requires a holistic understanding of the material, the joining process and the resulting properties of the joint. In this paper, the process chain for clinching metal sheets is described and experimental techniques are proposed to analyze the process-microstructure-property relationships from the sheet metal to the joined structure. At the example of clinching aluminum EN AW 6014, characterization methods are applied and discussed for the following characteristics: the mechanical properties of the sheet materials, the tribological behavior in the joining system, the joining process and the resulting material structure, the load-bearing behavior of the joint, the damage and degradation as well as the service life and crack growth behavior. The compilation of the characterization methods gives an overview on the advantages and weaknesses of the methods and the multiple interactions of material, process and properties during clinching. In addition, the results of the analyses on EN AW 6014 can be applied for parameterization and validation of simulations.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Phase identification in twin-roll cast Al-Li alloys - BAJTOŠOVÁ, Lucia; Grydin, Olexandr; STOLBCHENKO, Mykhailo; Schaper, Mirko; KŘIVSKÁ, Barbora; KRÁLÍK, Rostislav; ŠLAPÁKOVÁ, Michaela; CIESLAR, Miroslav (METAL 2022 Conference Proeedings)
Al-Li-based alloys are an attractive material for aircraft and aerospace applications. Preparation of these alloys by twin-roll casting (TRC), which combines rapid metal solidification and subsequent plastic reduction in a single processing step, could improve the properties of the alloys compared to materials prepared by conventional direct-chill casting. A commonly used approach for identifying primary phases is a chemical analysis by energy dispersive spectroscopy (EDS). More accurate results can be achieved by combining the method with diffraction analysis. This process can be considerably simplified in microscopes equipped with automated crystal orientation and phase mapping (ACOM-TEM). Al-Cu-Li-Mg-Zr alloy was prepared by twin-roll casting. A combination of TEM and STEM images with chemical analysis by EDS and ACOM-TEM was used to obtain complex information about phases of boundary primary particles. The efficiency of the individual methods for the phase identification in TRC Al-Li-based alloys is discussed.
Keywords: Al-Cu-Li-M-Zr-Fe alloy; twin-roll casting; phase identification; ACOM-TEM

Co-bonding of carbon fibre-reinforced epoxy and galvanised steel with laser structured interface for automotive applications - Voswinkel, Dietrich; Striewe, Jan Andre; Grydin, Olexandr; Meinderink, Dennis; Grundmeier, Guido; Schaper, Mirko; Tröster, Thomas (Advanced Composite Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; Ceramics and Composites

Optical Detection of Phase Transformations in Steels: An Innovative Method for Time-Efficient Material Characterization During Tailored Thermo-mechanical Processing of a Press Hardening Steel - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract With an innovative optical characterization method, using high-temperature digital image correlation in combination with thermal imaging, the local change in strain and change in temperature could be determined during thermo-mechanical treatment of flat steel specimens. With data obtained by this optical method, the transformation kinetics for every area of interest along the whole measuring length of a flat specimen could be analyzed by the generation of dilatation curves. The benefit of this innovative optical characterization method compared to a dilatometer test is that the experimental effort for the design of a tailored component could be strongly reduced to the investigation of only a few tailored thermo-mechanical processed specimens. Due to the implementation of a strain and/or temperature gradient within the flat specimen, less metallographic samples are prepared for hardness analysis and analysis of the microstructural composition by scanning electron microscopy to investigate the influence of different process parameters. Compared to performed dilatometer tests in this study, the optical method obtained comparable results for the transformation start and end temperatures. For the final design of a part with tailored properties, the optical method is suitable for a time-efficient material characterization. Graphical Abstract
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

The influence of surface on direction of diffusion in Al-Fe clad material - Šlapáková, Michaela; Křivská, Barbora; Fekete, Klaudia; Králík, Rostislav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Materials Characterization)
Aluminium-steel clad composite was manufactured by twin-roll casting. An intermetallic layer of Al5Fe2 and Al13Fe4 formed at the interface upon annealing above 500 °C. During in-situ annealing in transmission electron microscope, the layer grew towards the steel side of the interface in tongue-like protrusions. A study of furnace-annealed samples revealed, that the bulk growth of the interface phase proceeds towards the aluminium side. The growth towards steel is a surface effect that takes place simultaneously with the bulk growth towards aluminium. At the beginning of the intermetallic layer formation diffusion of Fe into aluminium prevails, afterwards Al atoms diffuse throught the newly formed intermetallic layer towards steel and the whole interface shifts towards aluminium. The kinetics of growth of the intermetallic layer follows parabolic law in both cases, indicating that the growth is governed by diffusion.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Microstructure transformations in a press hardening steel during tailored thermo‐mechanical processing - Westermann, Hendrik; Reitz, Alexander; Mahnken, Rolf; Schaper, Mirko; Grydin, Olexandr (steel research international)

Influence of thermomechanical processing on the microstructural and mechanical properties of steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Materials Science and Engineering: A)
In order to reduce CO2 emissions in the transport sector, the approach of load-adapted components is increasingly being pursued. For the design of such components, it is crucial to determine their resulting microstructure and mechanical properties. For this purpose, continuous cooling transformation diagrams and deformation continuous cooling transformation diagrams are utilized, however, their curves are strongly influenced by the chemical composition, the initial state and especially the process parameters. In this study, the influence of the process parameters on the transformation kinetics is systematically investigated using an innovative characterization method. The experimental setup allowed a near-process analysis of the transformation kinetics, resulting microstructure and mechanical properties for a specific process route with a reduced number of specimens. A systematic investigation of the effects of different process parameters on the microstructural and mechanical properties made it possible to reveal interactions and independencies between the process parameters in order to design a partial heating or differential cooling process. Furthermore, the implementation of two different cooling conditions, representative of differential cooling in the die relief method with tool-contact and non-contact areas, showed that the soaking duration has a significant influence on the microstructure in the non-contact tool area.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Numerical and Experimental Investigation of Heat Transfer in the Solidification-Deformation Zone During Twin-Roll Casting of Aluminum Strips - Grydin, Olexandr; Mortensen, Dag; Neuser, Moritz; Lindholm, Dag; Fjaer, Hallvard G.; Schaper, Mirko (Light Metals 2022)